Rev. Stats. of the State of Del. to the Year of Our Lord One Thousand Eight Hundred and Fifty-two, 333 (Dover, Delaware 1852) § 13 - (:unkn) unknown (General Publisher, 1852)
Authorized the justices of the peace to arrest and bind to surety all affrayers, breakers and disturbers of the peace, and all who go armed offensively to the terror of the people, or are otherwise disorderly and dangerous. Note as of 10/26: Duke left out a significant, material portion of this law. Affrayers, breakers and disturbers of the peace was not included on Duke's page.
--
Keywords: CARRY - DANGEROUS PERSONS